2019
DOI: 10.1074/jbc.ra119.009675
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CD44 induces apoptosis, inflammation, and matrix metalloproteinase expression in tendinopathy

Abstract: Apoptosis has emerged as a primary cause of tendinopathy. CD44 signaling pathways exert anti-apoptotic and-inflammatory effects on tumor cells, chondrocytes, and fibroblast-like synoviocytes. The aim of this study was to examine the association among CD44, apoptosis, and inflammation in tendinopathy. Expression of CD44 and apoptotic cell numbers in tendon tissue from patients with long head of biceps (LHB) tendinopathy were determined according to the histological grades of tendinopathy. Primary tenocytes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 33 publications
3
35
0
1
Order By: Relevance
“… 15 Our previous studies showed that CD44 mediated HA-induced downregulation of MMP-1 and -3 expression in IL-1β-stimulated tenocytes and that inhibition of the CD44 pathway using an antagonizing antibody induced pro-inflammatory cytokine and MMP expression in rat tendinopathic tenocytes. 16 , 17 Therefore, our second hypothesis was that CD44 protects tenocytes from cell senescence under tendinopathic conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Our previous studies showed that CD44 mediated HA-induced downregulation of MMP-1 and -3 expression in IL-1β-stimulated tenocytes and that inhibition of the CD44 pathway using an antagonizing antibody induced pro-inflammatory cytokine and MMP expression in rat tendinopathic tenocytes. 16 , 17 Therefore, our second hypothesis was that CD44 protects tenocytes from cell senescence under tendinopathic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies demonstrated CD44 ’s role in the extravasation and recruitment of lymphocytes to the lungs, kidneys, and joints in inflammatory diseases [ 79 ], including sepsis, chronic kidney disease [ 80 ], cardiac fibroblast [ 81 , 82 ], and SLE [ 83 ]. It binds to hyaluronic acid for downstream signaling, and is committed to host–pathogen interactions [ 84 ]. It has been reported that the inhibition of CD44 ’s function effectively reduced the buildup of neutrophils in the lungs in abdominal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…During intrinsic repair, the injury site has low ratio of TGF-β1/TGF-β3, which is opposite to extrinsic repair (Ferguson and O'Kane, 2004). During extrinsic repair, excessive inflammatory response causes disruption of tendon ECM homeostasis, resulting in fibrosis and adhesive scar formation (Wu et al, 2019). Fibrosis and adhesive scar formation cause loss of biomechanical properties, which make these an extremely serious problem.…”
Section: Immune Response Drives Tendon Repairmentioning
confidence: 99%